PATTERNS AND BELIEFS OF ISAN TATTOO - Kamonwan Pongkul; Dr. Pat Kotchapakdee; Dr. Kittsan Sriruksa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This article was a part of research titled Isan Tattoo: Pattern and Beliefs for Fashion design which aimed to study the patterns and beliefs of Isan Tattoo. The study had collected data from literature reviews and field study i.e. survey, observation, interview, included target population such as key informants, casual informants, and general informants. The study results were analyzed by the aesthetic and semiology theory, then presented by descriptive analysis. The study results indicated that the Isan Tattoo was found in four ethnics, namely, Tai-Lao, Nyaw, Phu Tai, and Khalerng ethnic groups which can be divided into three prototypes as were follows: 1) Image tattoo, 2) Pattern tattoo, and 3) Mystic symbol from the four ethnics. These prototypes reveal that the tattoos were applied from natural material and household usage stuffs, namely, Creeper, Flower, Lotus, Pliers cutting, Geometric, Pineapple, Dog tooth, Ikat, Tamarind leaf, Cross, Composition, Circular, Scratch, Leaf, Fish scale, Decorative, Elephant nail, Serration, Star, Zigzag, and applied pattern which different in each ethnic group including, animals such as Mom (mythical animal) and bird for artistry purpose, the mom was embedded with all ethics based on shared characteristic among the ethnics. Moreover, the Mystic symbol tattoo in arm and body areas was embedded with the belief of incantations and significant tradition.